Midwives’ adherence to targeted postpartum care guidelines on immediate postpartum assessment at public hospitals in Migori County, Kenya - Omiah, Gladyce A.; M. Karonjo, Jane; Ritho, Muthoni (International Journal Of Community Medicine And Public Health, 2025)
Background: A maternal death occurs globally every two minutes due to pregnancy or childbirth complications. Risk is highest in Sub-Saharan Africa (1:41) compared to the developed world (1:5300). The postpartum period accounts for 60% of maternal deaths, with half occurring within 24 hours after birth, mainly from postpartum hemorrhage and eclampsia. Many of these deaths are linked to suboptimal immediate postpartum assessment (IPPA). This study assessed midwives’ adherence to the targeted postpartum care (TPPC) guideline on IPPA in public hospitals in Migori County, Kenya. Methods: An analytical cross-sectional study was conducted among midwives in level 4 public hospitals in the period September 2023 to April, 2024. Sample size was calculated using Yamane’s formula. Purposive sampling was used for hospital selection, and simple random sampling for participants. Participants with active practicing license and at least three months of experience in a maternity ward or MCH clinic were included. Those on orientation or internship, with expired licenses, or on leave were excluded. Data were collected via structured questionnaires and analyzed using SPSS version 28. Descriptive statistics included means and percentages; inferential analysis used logistic regression and Chi-square with significance at p<0.05 and p<0.05 respectively. Results: Midwives’ adherence to the TPPC guideline was moderate (65.48%). Age (p=0.014), experience (p=0.040), CPD frequency (p=0.018), and awareness of the guideline (p=0.034) were significantly associated with adherence. Conclusions: Moderate adherence was observed, with CPD, age, experience, and guideline awareness influencing compliance. Full adherence is vital for improving maternal outcomes and reducing preventable deaths. Strengthening IPPA enforcement and targeted CPD on identified gaps is critical for enhanced adherence.